2018
DOI: 10.1007/s42770-018-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of culturable microbiota present in the stomach of children with gastric symptoms

Abstract: Despite extensive studies on the gastric microbiota, including Helicobacter pylori and non-H. pylori, the bacterial composition in children remains unknown. In this study, we analyzed the culturable gastric bacteria in stomach biopsies from 346 children aged 1-15 years affected by gastric diseases. H. pylori and non-H. pylori were identified by specific PCR and 16S rDNA sequencing, respectively. Antibiotic susceptibilities of H. pylori and non-H. pylori were tested by the E-test and disk diffusion methods, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Some previous studies reported differences in the positive rate of H pylori infection between males and females, while some others reported no difference. 23,24 H pylori infection status also changed depending on different regions and populations, such that the difference between males and females also varied.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies reported differences in the positive rate of H pylori infection between males and females, while some others reported no difference. 23,24 H pylori infection status also changed depending on different regions and populations, such that the difference between males and females also varied.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of pediatric patients, scarce information is available regarding the composition of gastric flora. A recent study performed on 346 children with symptoms suggesting H. pylori infection that aimed to assessed both H. pylori and non- H. pylori strains, pointed out 114 H. pylori positive cases and identified 366 non- H. pylori genera from 189 gastric biopsy specimens, 247 Gram-positive and 119 Gram-negative [ 42 ]. Moreover, the authors pointed out the following resistance rates for H. pylori strains: 86.4% for metronidazole, 36.4% for clarithromycin, 31.8% for levofloxacin, and 22.7% for both tetracycline and amoxicillin, as well as 10 multidrug-resistant strains [ 42 ].…”
Section: Innate Immunity and Gastric Microbiota—the ‘Yin And Yang’ Of H Pylori Infectionmentioning
confidence: 99%
“…A recent study performed on 346 children with symptoms suggesting H. pylori infection that aimed to assessed both H. pylori and non- H. pylori strains, pointed out 114 H. pylori positive cases and identified 366 non- H. pylori genera from 189 gastric biopsy specimens, 247 Gram-positive and 119 Gram-negative [ 42 ]. Moreover, the authors pointed out the following resistance rates for H. pylori strains: 86.4% for metronidazole, 36.4% for clarithromycin, 31.8% for levofloxacin, and 22.7% for both tetracycline and amoxicillin, as well as 10 multidrug-resistant strains [ 42 ]. Non- H. pylori bacteria identified in this pediatric cohort presented generally higher resistance rates to the same antibiotics: 94.8% for metronidazole, 46.7% for clarithromycin, 42.6% for amoxicillin, 26.2% in case of tetracycline and 15.3% for levofloxacin.…”
Section: Innate Immunity and Gastric Microbiota—the ‘Yin And Yang’ Of H Pylori Infectionmentioning
confidence: 99%
“…This number is rarely described in pediatric trials, also because of the high rate of antibiotic resistance of H pylori . Furthermore, high multiple resistance and secondary resistance rates significantly affect H pylori eradication . The prevalence of H pylori resistant to antibiotics differs among countries (Table ) and is usually explained by the different exposure to the corresponding antibiotics in each population .…”
Section: Diagnosismentioning
confidence: 99%
“…The prevalence of H pylori resistant to antibiotics differs among countries (Table ) and is usually explained by the different exposure to the corresponding antibiotics in each population . First‐line treatment should, therefore, be tailored according to the strain's susceptibility or, if tests are not available, at least according to the regional antibiotic resistance rates of H pylori strains …”
Section: Diagnosismentioning
confidence: 99%